The evaluation of Brunei Bay sediment cores sedimentation rate using 210Pb radiometric dating technique - Islam, Mir Sujaul; Joseph, Bidai; Ghazali, Adiana; Noor Azhar, Mohd Shazili; Ong, M. C.; Hafizan, Juahir; Hasrizal, Shaari; Yii, Mei Wo; Mohd Khairul Amri, Kamarudin; Muhammad Barzani, Gasim; Khairul Nizam, Abdul Maulud (Science Publishing Corporation, 2018)
The use of radioisotopes 210Pb and 226Ra in establishing the geochronology of pollutants in the sediment core and sediment dating is be-ing widely used in the world. The present study was conducted in Brunei Bay region of Malaysian waters to define the sedimentation rate and sediment age as well as to investigate the possible sources of pollutants into this bay. Sediment core samples were cut by layers, dried and analyzed using High Purity Germanium (HPGe) Spectrometer. Results obtained marked the time interval of 1875, 1956, 1962 and 1945 for sediment core B5, B9, B13 and LB consecutively. Sediment core of B9 and LB showed higher sedimentation rate compared to B5 and B13 due to the rapid development of urban and industrial. The increasing of sedimentation rate over the last 25 years was in line with the increasing of human activities surround the bay. Additionally, the health and distribution of mangroves surround Brunei Bay were important to determine the sediment movement which will affect the sedimentation rate in the bay. Overall, by controlling human activities as well as sustaining the mangroves population, could maintain and preserve the natural and unique environment of Brunei Bay.